Design and Develop an Innovative Online Learning Environment - Kaur, Abtar (2011)
Designing an online learning environment can be challenging and daunting if one does not have the right knowledge to do so. So what constitutes right knowledge? Firstly, it is crucial that online facilitators/instructors have some knowledge in instructional design and related learning strategies. Then, it is important to know how to write impactful learning outcomes which will enable one to select the appropriate technology tools. Selection of tools may not be sufficient, it is important to discuss about examples of how all these designs form a viable and innovative learning. Understanding that different pedagogical methods will give rise to the use of a variety of technology tools and techniques that encourage students to learn suited to their learning styles and level of interactivity is an important aspect of this workshop. From here, participants will be given tasks to apply the various concepts and strategies to design and develop their own online learning environments. (Abstract by authors)